Detecting laryngopharyngeal reflux in patients with upper airways symptoms: Symptoms, signs or salivary pepsin? - Spyridoulias, Alexander; Lillie, Siobhan; Vyas, Aashish; Fowler, Stephen J. (Respiratory medicine, 2015)
Laryngopharyngeal reflux (LPR) can induce laryngeal hyper-responsiveness, a unifying feature underlying chronic cough and vocal cord dysfunction. The diagnosis of LPR currently relies on invasive oesophageal pH impedance testing. We compared symptoms, laryngeal signs and salivary pepsin as potential diagnostic methods for identifying LPR in patients with upper airway symptoms. Symptoms were assessed using the Reflux Symptom Index (RSI) and signs of laryngeal inflammation quantified using the Reflux Finding Score (RFS) during laryngoscopy. Saliva samples were analysed for the presence of pepsin. A sub-group of patients with severe symptoms and signs of LPR were investigated with oesophageal pH monitoring and impedance study. Seventy eight patients with chronic cough and/or suspected vocal cord dysfunction were recruited, mean (SD) age, 54.6 (15.6) years. The majority (87%) had significant symptoms of reflux (RSI>13). There were clinical signs of LPR (RFS>7) in 51% of cases. Pepsin was detected in the saliva of 63% of subjects and 78% of those with a high RFS. Salivary pepsin had a sensitivity of 78% and specificity of 53% for predicting a high RFS. There was a correlation between the RSI and RFS (r = 0.51, p < 0.001) and between the severity of laryngeal inflammation and the concentration of pepsin (r = 0.28, p = 0.01). All cases investigated with pH-impedance study had objective evidence of proximal reflux. Salivary pepsin may be used as a screening adjunct to supplement the RFS in the clinical workup of patients with extra-oesophageal symptoms and upper respiratory tract presentations of reflux. •Laryngopharyngeal reflux (LPR) can induce extra-oesophageal symptoms in the upper airways.•We compared patients' symptoms, laryngeal signs and salivary pepsin as potential markers of LPR.•Salivary pepsin concentration was significantly correlated with the severity of laryngeal inflammation.•Salivary pepsin had a sensitivity of 78% and specificity of 53% for predicting laryngeal signs.•This may be a useful test to supplement the clinical assessment of upper airway symptoms.